Covid-19 impact on credit risk to the banking sector in Malaysia: comparative analysis between conventional and Islamic banking - Lim, Jee Yi; Poh, Tun Lin; Khoo, Wendy Hui Wen; Wong, Kar Xin (2022)
The COVID-19 pandemic has affected various commercial segments in Malaysia, banking industry as one of the sectors that facing the credit risk because of this issue. The objective of this study is to assess the impact of COVID-19 on the credit risk to the conventional, Islamic, and overall banking in Malaysia. The independent variables comprise total credit/total financing, Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) / Financing to Deposit Ratio (FDR) and Return on Asset (ROA). For the data collection, the research data of this study is attained and re-purposed to investigate the existing data by analyzing the annual report from 2011 to 2021 for nine conventional and nine Islamic banks in ten years of balanced data. All the descriptive data collected is analysed by using EViews, Panel Data Regression, Fixed Effect Model (FEM), and Random Effect Model (REM) were used as the regression model in this study. Besides, Hausman Test is applied in this study to determine which model is suitable and appropriate for this study. The finding shows that COVID-19 has a significant relationship with the credit risk to the banking sector in Malaysia. For the Islamic bank model, the total financing and capital adequacy ratio are the most significant variables. While for the conventional bank model, the total credit and capital adequacy ratio are the main essential variables. In sort, a total credit or total financing, and CAR are the most significant variables for the overall banking system.